PEMANFAATAN JAMUR TIRAM SEBAGAI SALAH SATU SUMBER GIZI ALTERNATIF BAGI MASYARAKAT - Mareko Giawa (Universitas Nias Raya, 2023)
Oyster mushroom (Pleurotus sp.) is a mushroom that can be used as food (Edible mushroom). Besides having a good taste, Pleurotus sp. It also has high nutritional value. This type of research is a descriptive type of qualitative research. This research was carried out from 01 to 30 July 2022, this research was carried out in Telukdalam Village, South Nias Regency. Nutritional science is the study of the relationship between food and health. Nutrition science covers a very broad scope. Based on the results of the research and discussion, it was found that (1) the technique or method of managing the oyster mushroom was managed by boiling, curry, soup and even mixed with noodles and several other types of food according to taste. (2) Oyster mushroom is a nutritional alternative. This is because from the findings of research that has been carried out by conducting interviews with several respondents, it is known that oyster mushrooms are not just food that has a good taste but besides having content such as water, protein, carbohydrates, calcium, energy, fat and phosphorus. which is very important for the needs of the body, also has properties such as lowering cholesterol and is very good for heart health. The suggestions from the researcher are as follows: (1) The researcher hopes that the results of this study can be used as a reference and help increase student knowledge in the learning process both in terms of theory and practicum. (2) people should be wise and understand how to manage and cultivate mushrooms as food or food as an alternative source of nutrition and have health benefits.